2020
DOI: 10.1186/s12864-020-6619-8
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome resequencing of the Iranian native dogs and wolves to unravel variome during dog domestication

Abstract: Background: Advances in genome technology have simplified a new comprehension of the genetic and historical processes crucial to rapid phenotypic evolution under domestication. To get new insight into the genetic basis of the dog domestication process, we conducted whole-genome sequence analysis of three wolves and three dogs from Iran which covers the eastern part of the Fertile Crescent located in Southwest Asia where the independent domestication of most of the plants and animals has been documented and als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
0
4
0
1
Order By: Relevance
“…S7–S9 , Supplementary Material online ), as well as between IW01 and three more recently reported Iranian wolves ( supplementary fig. S10 , Supplementary Material online ) ( Amiri Ghanatsaman et al 2020 ). Admixture among these lineages is expected, given the lack of reproductive barriers and any major geographic barriers separating these populations.…”
Section: Resultsmentioning
confidence: 99%
“…S7–S9 , Supplementary Material online ), as well as between IW01 and three more recently reported Iranian wolves ( supplementary fig. S10 , Supplementary Material online ) ( Amiri Ghanatsaman et al 2020 ). Admixture among these lineages is expected, given the lack of reproductive barriers and any major geographic barriers separating these populations.…”
Section: Resultsmentioning
confidence: 99%
“…Conservation occurs in coding and noncoding regions, such as the promoter, which acts as a regulatory element to control gene transcription (Lindblad‐Toh et al., 2005 ). According to a study on the canine genome, the majority of the variations are found in the intergenic (53.79%) and intronic (34.4%) regions, with less variation found in the exonic (0.25%) and transcript (0.002%) regions of the genes (Amiri Ghanatsaman et al., 2020 ). The lack of mutation within the screened regions of the BDNF and CCK genes may be attributed to the sequence conservation of targeted functional elements and the specialised role of these loci in the studied canine population.…”
Section: Discussionmentioning
confidence: 99%
“…A member of interleukins (IL18) and TYK2 were present in one of the candidate regions identified in Arab and Oromo goat populations. Interleukins are expressed by leukocytes (Maggio et al, 2006) and are likely involved in the activation of the immune response of goats (Amiri et al, 2023) and chickens (Susta et al, 2015;Chen et al, 2016;Truong et al, 2016). In a study conducted on Malabari goats during heat stress, IL18 was identified as a reliable immunological marker that aids in assessing heat stress-mediated immune response alterations (Rashamol et al, 2019).…”
Section: Immune Response Genesmentioning
confidence: 99%